Natural Window of Opportunity? Low-Income Parents' Responses to Their Children's Impending Kindergarten Entry - Christina Weiland; Dana Charles McCoy; Elizabeth Grace; Soojin Oh Park (SAGE Publishing, 2017)
Parental investments in the activities and materials that drive learning are central to young children's school readiness and life success. Little is known, however, about how parents adjust these investments in response to outside pressures, including their children's impending entry into kindergarten. In the present study, we employ two analytical strategies (multilevel residualized change and regression discontinuity) within national data from the Head Start Impact Study to examine whether parents of children facing an impending entry to kindergarten invest more time and materials in their children's language and literacy skill development compared with parents of otherwise similar children who are not yet facing formal school entry. Results suggest that low-income parents react to the impending kindergarten transition by increasing their provision of parent-child language and literacy activities (d = .15) but not related materials. We discuss the implications of our findings for the timing of parenting interventions.